KAJIAN KEMAMPUAN KONEKSI MATEMATIK SISWA SMP DI KOTA BANDUNG PADA MATERI ARITMETIKA SOSIAL - nur hasanah; Devi Yuliani; eva dwi minarti; euis eti rohaeti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
The ability of mathematical connections is an essential skill that must be mastered by high school students, as it will help master understanding of meaningful concepts and help solve mathematical problems through the interrelationship between mathematical concepts and between mathematical concepts and concepts in other disciplines even with applications in real-life students. This study aims to examine the ability of mathematical connections of students in one junior high school in Bandung on Social Arithmetic materials. The method used in this study is descriptive qualitative, with the subject of research is 36 students of class VIII in one of the State Junior High School in Bandung. Instrument given in the form of description test as much as 3 problem each representing indicator ability and analyzed so that get data fulfillment indicator ability of mathematic connection. Based on the data analysis, the students 'mathematical connection ability is still low, so it is necessary to design the learning activities that can facilitate students' mathematical connection ability.